2014
DOI: 10.1016/j.nrleng.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ankle-foot orthosis on postural control after stroke: A systematic review

Abstract: Introduction: Stroke is currently the main cause of permanent disability in adults. The impairments are a combination of sensory, motor, cognitive and emotional changes that result in restrictions on the ability to perform basic activities of daily living (BADL). Postural control is affected and causes problems with static and dynamic balance, thus increasing the risk of falls and secondary injuries. The purpose of this review was to compile the literature to date, and assess the impact of ankle-foot orthosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…In the next step, 37 potentially relevant studies were then identified and evaluated by the two reviewers independently based on the full text. Finally, 14 studies 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 were selected by the research team to enter the study (Figure 1 ). In the final step, 23 studies were excluded, along with the reasons for exclusion, which are listed in Supporting Information: Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the next step, 37 potentially relevant studies were then identified and evaluated by the two reviewers independently based on the full text. Finally, 14 studies 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 were selected by the research team to enter the study (Figure 1 ). In the final step, 23 studies were excluded, along with the reasons for exclusion, which are listed in Supporting Information: Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, patients with weak plantarflexors may be hindered in generating adequate propulsion. In addition, recent studies have provided conflicting results as to whether AFOs reduce the risk of falling (Cakar et al, 2010; Guerra Padilla et al, 2011; Wang et al, 2007). Other studies have found no difference in clinical balance scores (Park et al, 2009; Wang et al, 2005) or in static or dynamic weight-bearing tasks when wearing an AFO (Simons et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…has been considered to treat patients with spastic paralysis of the upper limbs and has demonstrated good clinical results. Non-invasive rehabilitation, such as extracorporeal shock wave therapy, use of orthosis, neuromuscular electrical stimulation therapy and virtual reality, among other treatments, is currently the focus of treatment for patients with lower limb dysfunction 26–29. Although these methods have some effect on the recovery of the ability to walk, they cannot directly restore the muscle strength in the lower limbs, and patients tend to rely on the assistance of a walker.…”
Section: Discussionmentioning
confidence: 99%